Systematic Literature Review and Meta-Analysis of the Relationship Between Polyunsaturated and Trans Fatty Acids During Pregnancy and Offspring Weight Development - Ren, Xuan; Vilhjálmsdóttir, Birgitta Lind; Rohde, Jeanett Friis; Walker, Karen Christina; Runstedt, Suzanne Elizabeth; Lauritzen, Lotte; Heitmann, Berit Lilienthal; Specht, Ina Olmer (Frontiers in Nutrition, 2021)
Eicosapentaenoic acid (EPA), docosahexaenoic acid (DHA) and trans fatty acids (TFAs) may have an impact on offspring weight development. We conducted a systematic review and meta-analysis according to PRISMA guidelines to evaluate whether levels of these fatty acids during pregnancy influenced offspring weight development. Randomized controlled trials (RCTs) with DHA and/or EPA supplementation or cohort studies, which examined levels of DHA, EPA or TFAs in maternal or neonatal blood samples and recorded offspring weight were included. Overall, 27 RCTs and 14 observational studies were identified. The results showed that DHA and/or EPA supplementation doses >650 mg/d resulted in slightly higher birth weight (MD 87.5 g, 95%CI 52.3 to 122.6, n=3831) and combined BMI and BMI z-score at 5-10 years (SMD 0.11, 95%CI 0.04 to 0.18, n=3220). These results were rated as moderate quality. Results from the observational studies were generally inconsistent. High TFA levels during pregnancy seemed associated with lower birth weight. Finally, this review and meta-analysis supports a relationship between high maternal or neonatal DHA and/or EPA levels and higher offspring birth weight and weight in childhood. More high-quality long-term studies are still needed.